(untitled) (Fiep Bulletin - online, 2014)
The aquatic environment due to its specific characteristics appears to be appropriate for diagnosing not only the swimming performance, but also the physical fitness of the population. The aim of this study is to determine the time duration and the body response to the load in the new 100 Steps test in deep water. We assessed the impact of the environment on heart rate. The results of comparison of the heart rate values measured in a sitting position on land and in deep water did not show statistically significant differences. Changes in heart rate before and immediately after the test, as well as changes immediately after the test and 3 minutes after the test were statistically significant in all groups of subjects. We note that the heart rate after a 3-minute rest did not fall to its initial level. On the basis of our results and in accordance with other authors we believe that the new test can be recommended as an appropriate means for monitoring physical fitness of the population in the aquatic environment.